Investigation on Silver Modification of Different Shaped Filler on the Heat Conduction Performance Improvement for Silicone Elastomer - Li, Yifan; Zhang, Yuan; Liu, Yicheng; Xie, Huaqing; Yu, Wei (Frontiers in Thermal Engineering, 2022)
The continuous miniaturization and multi-function of electronic devices have put forward high requirements for the effective removal of the heat generated in the system. Developing thermally conductive polymer composite-based thermal interface materials is becoming the research hotspot. In addition to the usually concerned intrinsic thermal conductivity of the filler itself, surface modification is one of the important ways to form an effective heat conduction pathway and improve the overall thermal conductivity of materials. In this work, we used silicon rubber as the polymer matrix and achieved the thermal conductivity increment via various fillers with different shapes. The adopted fillers are spherical aluminum oxide (Al2O3), linear carbon fiber (CF), and boron nitride (BN) sheets, which can be considered as zero-dimensional (0D), one-dimensional (1D), and two-dimensional (2D) fillers respectively. We also prepared the silver-modified fillers and investigated the influence on the formation of heat conduction pathways and interfacial thermal resistance (ITR) of different shaped fillers. An obvious increment in thermal conductivity of the composite with silver-modified fillers was observed compared to the composite with pristine fillers. Furthermore, through the practical thermal management performance investigation, we found the thermal conductivity increment did improve the actual heat transfer performance of composite elastomers functioning as thermal interface materials (TIMs).